Humic acids‐based biostimulants impact on root viability and hormone metabolism in creeping bentgrass putting greens. Issue 1 (9th March 2021) - Zhang, Xunzhong; Goatley, Mike; McCall, David; Kosiarski, Kelly; Reith, Frank
Abstract: Creeping bentgrass putting greens experience quality decline during summer due to heat and drought stress in U.S. transition zone and other areas with similar climate. Plant biostimulants have been used to improve turfgrass tolerance to abiotic stress. This study was designed to investigate the effect and modes of action of humic acid (HA) based biostimulants on turf quality, root viability, and hormone metabolism of creeping bentgrass during summer stress. The two humic acid formulations – solid powder and liquid, were characterized and applied at two rates of each formulation to a creeping bentgrass putting green from May through August in this study. Auxin indole‐3‐butyric acid (IBA) served as the positive control. Foliar application of either solid or liquid HA at 0.2% and 0.3% biweekly improved turf quality, photochemical efficiency and chlorophyll content at certain sampling dates. The HA treatments also increased leaf growth hormone cytokinin zeatin riboside (ZR) on July 25 and August 22 and auxin indole‐3‐acetic acid (IAA) on August 22. The HA treatments improved root length, surface area (SA), root volume, biomass, and viability. Solid HA (HA‐S) at 0.2%, 0.3% solution, liquid HA (HA‐L) at 0.2%, and 0.3% increased root viability by 91.8%, 122.4%, 57.1%, and 71.4%, respectively, when compared to the control. This study suggests foliar application of humic acid‐based biostimulants may be considered as an effective tool to improve turf performance in creeping bentgrass putting greens during summer months.